A Survey of Fruit Trees Species in an Urban Community in Ekiti State, Nigeria - Iyanuoluwa Kikelomo Ajayi; Joshua Kayode (Budapest International Research and Critics University, 2020)
A rapid appraisal technique was used to survey fruit trees species in Ifaki-Ekiti, an urban community in Ekiti State, Nigeria. The three major routes in the town and three educational institutions were sampled. Fruit trees within each stratum were identified to species level, counted and recorded. Similarity indices and indices of diversity in the occurrences of the species were determined among the strata. The perceptions of residents on the fruit trees were also determined through the use of a semi- structured questionnaire matrix administered on 20 randomly selected individuals in each of the stratum. Respondents’ indigenous knowledge on the species were determined and recorded. 96 fruit trees individuals belonging to 9 species and 6 families were sampled. The family Anacardiaceae has the highest number of species. The most frequently occurring species along the routes were Carica papaya, Anacardium occidentale, and Citrus sinensis with 12,10 and 8 individuals respectively and for the educational institutions were Anacardium occidentale, Mangifera indica and Carica papaya with 26,17 and 8 individuals respectively. 87% of the respondents were familiar with the cultivation of fruit trees and 67% of respondents were involved in planting of fruit trees in their household environment. Preference was skewed towards planting of fruit trees as food, source of vitamins and source of income. Strategies that could improve fruit tree diversity in the study area were proposed.